2017
DOI: 10.1186/s12904-017-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved family members’ perceptions of the quality of end-of-life care across four types of inpatient care settings

Abstract: Background: The aims of this study were to gain a better understanding of how bereaved family members perceive the quality of EOL care by comparing their satisfaction with quality of end-of-life care across four different settings and by additionally examining the extent to which demographic characteristics and psychological variables (resilience, optimism, grief) explain variation in satisfaction. Methods: A cross-sectional mail-out survey was conducted of bereaved family members of patients who had died in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…The factors associated with the quality of EOLC in the ICU were found in the remaining 18 descriptive studies. 63 -80…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors associated with the quality of EOLC in the ICU were found in the remaining 18 descriptive studies. 63 -80…”
Section: Resultsmentioning
confidence: 99%
“…The second finding was identification of factors (patients/family members’ characteristics and characteristics of the ICU setting) associated with families’ perceptions (see Table 4), which were identified in 18 descriptive studies with large sample sizes in multinations. 63 -80 Seven studies showed the most common factor for families’ evaluation of the quality of EOLC was the location where the patients received EOLC. 64 -67,73,75,76 The ICU is a common place of death but was not the preferred place to die for patients and family members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of care provided to individuals at the end of life, and to their family members, has become an important health and social issue across the world [1]. Quality end-of-life care is considered a right for all citizens and the responsibility of every government [2].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how care is perceived by family members across care settings is essential to identify specific domains of care that need to be improved [1] and that influence how end-of-life care is delivered and experienced [6].…”
Section: Introductionmentioning
confidence: 99%